Evaluasi Pasca Huni Perumahan Nelayan di Desa Labuhan Lalar Kabupaten Sumbawa Barat - Muhammad Luthfie; Agam Marsoyo (Universitas Muhammadiyah Palembang, 2024)
The village of Labuhan Lalar is a village with the highest number of fishermen in West Sumbawa Regency. In 2015, the government initiated the construction of housing specifically for the fishermen community there. After being relocated to these fishermen's housing and living there for the past 8 years, it is necessary to reassess the extent to which the performance of this housing has impacted the lives of its residents. The post-occupancy evaluation in this study aims to assess the housing's performance in supporting the health of its occupants. This research employs a deductive quantitative approach. The evaluation in this study falls under the post-implementation evaluation phase (ex-post) conducted after the plan has been implemented. The results indicate that technical elements such as humidity, ventilation, noise, flooring, roofing, and walls of the housing did not perform well in supporting the health of the fishermen's housing residents, leading to a decline in health post-occupancy. This finding could serve as input for the development of new standards and regulations to better address health aspects in housing design and construction. This could influence potential occupants’ preferences before purchasing, renting, or building their own homes with a focus on health considerations.